Ultrahigh energy storage performance of all-organic dielectrics at high-temperature by tuning the density and location of traps. Issue 12 (21st September 2022) - Feng, Mengjia; Feng, Yu; Zhang, Changhai; Zhang, Tiandong; Chen, Qingguo; Chi, Qingguo
Abstract : An improved composite dielectric with an excellent high-temperature energy storage performance has been obtained by modulating the trap parameters. Abstract : Improving the tolerance of flexible polymers to extreme temperatures and electrical fields is critical to the development of advanced electrical and electronic systems. Suppressing carrier movement at high temperatures is one of the key methods to improve the high-temperature charging and discharging efficiency. In this work, a molecular semiconductor (ITIC) with high electron affinity energy is blended into the promising polymer polyetherimide (PEI). This molecular semiconductor will introduce traps in the dielectric that can trap carriers, thus achieving the effect of inhibiting carrier movement. Changing the concentration and position of the molecular semiconductor by electrospinning technology also means changing the density of the trap and the position of the trap layer. The effects of trap density and trap layer location on the high-temperature breakdown strength and energy storage properties of composite dielectrics are studied successively, and the structure of a composite with optimal high temperature energy storage properties is obtained. That is, the dielectric S-15-28 has an energy storage density ( U ) of 6.37 J cm −3 at a temperature of 150 °C with a charge–discharge efficiency ( η ) of 90%; it also has a U of 4.3 J cm −3 at a temperature of 180 °C with the η of 90%. A mechanism based on Mott and Gurney's law is proposed to explain the effect of trap parameters on leakage current. This work provides a new structural design idea to regulate the dielectric properties of all-organic dielectrics through trap distribution parameter optimization.